2019
DOI: 10.1039/c9dt02435b
|View full text |Cite
|
Sign up to set email alerts
|

Bis(diphenylphosphinyl)-functionalized dipyrido-annulated NHC towards copper(i) and silver(i)

Abstract: Sterically rigid bis(phosphinyl)dipyrido-annulated NHC coordinates with Ag(i) and Cu(i) centres to form luminescent multinuclear complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…and Kunz et al Both theoretical and experimental studies have shown that its aromatic dipyrido moieties contribute to empty p orbitals of the carbene carbon, resulting in a higher π-donating ability in comparison to Arduengo-type NHCs . Previously, we have successfully introduced thio, phosphinyl, and aryl substituents to the dpa NHC backbone. The aryl-substituted dpa Ar2 NHCs were in situ generated by deprotonation of the respective imidazolium salt and characterized by complexation to a gold­(I) center (Scheme ).…”
Section: Resultsmentioning
confidence: 98%
“…and Kunz et al Both theoretical and experimental studies have shown that its aromatic dipyrido moieties contribute to empty p orbitals of the carbene carbon, resulting in a higher π-donating ability in comparison to Arduengo-type NHCs . Previously, we have successfully introduced thio, phosphinyl, and aryl substituents to the dpa NHC backbone. The aryl-substituted dpa Ar2 NHCs were in situ generated by deprotonation of the respective imidazolium salt and characterized by complexation to a gold­(I) center (Scheme ).…”
Section: Resultsmentioning
confidence: 98%
“…Triphenylphosphine selenide is the byproduct of this reaction, which was conveniently removed from the reaction mixture. Complexes 1-4 were characterized by elemental analysis, FT-IR, multinuclear NMR ( 1 H, 13 C, 11 B, 19 F and 31 P), and single-crystal X-ray techniques.…”
Section: Resultsmentioning
confidence: 99%
“…In 13 C NMR, the carbene carbon of 1-4 resonates around 187.6-187.7 ppm, which is considerably downfield shifted compared to L (154.4 ppm) and tetra coordinated Cu(I) complex [Cu(dptn)(dppe)] + (PF 6 À ), dptn = 2,4-dimethyl-8-phenyl-triazolo naphtyridine-9-ylidine, dppe = 1,2-bis(diphenylphosphino)ether (180.9 ppm). [12] The 31 P NMR chemical shift values of triphenylphosphines in 1-4 appeared around 4.50-4.59 ppm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noticed that the formation of the complexes with two identical Group 11 metal atoms bridged by a carbene ligand is well known [231][232][233][234][235][236][237][238][239][240][241][242][243][244]. At the same time, the examples of similar heterometallic systems have not been found, which can indirectly evidence their low stability.…”
Section: Possible Mechanisms and Driving Forces Of Transmetalation And Related Processesmentioning
confidence: 99%